Phonostylistic Resources in the Poetry of Mário Quintana - Távora, Antônio Duarte Fernandes (Entrepalavras, 2024)
This article examines the use of phonostylistic resources, proposed mainly by Monteiro (2009), and incorporates the theoretical insights of Gaya (1988) and Grammont (1971). This provided us with a model of analysis for the “expressive potentialities of phonemes” described by these authors, reflected in the poetry of Mário Quintana. The universe of the research is the book 80 Anos de Poesia by Mário Quintana, which condenses, in the organizer’s view, the most significant elements in nine books by the author. The delimitation of the universe of this research is limited to nine poems, one from each publication of the anthology of nine books that make up 80 Anos de Poesia. The objective is to explore how Quintana’s poetry reflects these phonostylistic structures – whether consciously or unconsciously – in order to discover how the expressive elements based on phonemes are actualized within the selected poems. We conclude that phonostylistic values can transcend their phonemic origin and be transferred to the graphic level, in which the written form of words continues to carry the aesthetic value previously transmitted by the phoneme.